2021
DOI: 10.1021/acs.cgd.1c00494
|View full text |Cite
|
Sign up to set email alerts
|

A Density-Functional Theory Structural Database for Discovery of Novel Actinide Waste Forms

Abstract: While high-level nuclear waste is effectively incorporated into borosilicate glasses for disposal, issues remain for handling transuranic (TRU) elements. Computational methods can be used to increase the efficiency for novel waste form discovery that can sequester specific species within different waste streams. Density-functional theory databases, such as the Materials Project and the Open Quantum Materials Database, have aided in the discovery of new materials with targeted properties. This paper discusses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Previous work by our group demonstrated that one can use the host structure for density functional theory (DFT) calculations that determine the 0 K heat of formation of hypothetical TRU containing compositions. For example, DFT calculations for A 2 M IV Si 6 O 15 (A = Na, K, Rb, Cs; M = Ce, Th, U, Np, Pu) compositions correctly predicted the stability of Cs 2 PuSi 6 O 15 , leading to the synthesis and structure determination of Cs 2 PuSi 6 O 15 . , To extend this work to a new family of silicate structures, we again employed DFT calculations to predict the 0 K formation enthalpies for the silicate fluoride structures reported herein. We are applying this methodology as an early screening tool to build on our previous work that demonstrated the utility of DFT-computed formation enthalpies for yielding dependable estimations of the relative stability of TRU containing silicates in order to follow up, when warranted, with attempts at synthesizing the TRU containing compositions. , …”
Section: Introductionmentioning
confidence: 83%
“…Previous work by our group demonstrated that one can use the host structure for density functional theory (DFT) calculations that determine the 0 K heat of formation of hypothetical TRU containing compositions. For example, DFT calculations for A 2 M IV Si 6 O 15 (A = Na, K, Rb, Cs; M = Ce, Th, U, Np, Pu) compositions correctly predicted the stability of Cs 2 PuSi 6 O 15 , leading to the synthesis and structure determination of Cs 2 PuSi 6 O 15 . , To extend this work to a new family of silicate structures, we again employed DFT calculations to predict the 0 K formation enthalpies for the silicate fluoride structures reported herein. We are applying this methodology as an early screening tool to build on our previous work that demonstrated the utility of DFT-computed formation enthalpies for yielding dependable estimations of the relative stability of TRU containing silicates in order to follow up, when warranted, with attempts at synthesizing the TRU containing compositions. , …”
Section: Introductionmentioning
confidence: 83%
“…Specifically, we employed the rotationally invariant approach of Dudarev et al with the Hubbard correction of 4.0 eV on the plutonium atoms . This choice of correction was found to be consistent with the previously recognized methods used for the development of the structural database of the Center for Hierarchical Waste Form Materials as well as the Open Quantum Materials Database …”
Section: Methodsmentioning
confidence: 99%
“…To investigate the phase stability of transuranic element containing borate salts, we selected Na 3 Nd­(BO 3 ) 2 (space group P 2 1 / n ), Na 3 Tm­(BO 3 ) 2 (space group P 2 1 / n ), K 3 Nd­(BO 3 ) 2 (space group Pnma ), and K 3 Tm­(BO 3 ) 2 (space group Pnnm ) as unique parent structures and substituted Nd and Tm with Am and Cm (as well as Np and Pu) to construct the daughter compounds. We have followed the established methods by the Open Quantum Materials Database (OQMD) and Center for Hierarchical Waste Form Materials (CHWM) structural database to examine the energetics of parent and daughter prototypical structures. Electronic structure calculations were performed with density functional theory (DFT) , using the projector augmented-wave (PAW) method as implemented in the Vienna Ab initio Simulation Package (VASP). Our calculations used the Perdew–Burke–Ernzerhof (PBE) for the exchange–correlation functional.…”
Section: Methodsmentioning
confidence: 99%